Farming Systems, Food Security and Farmers' Awareness of Ecosystem Services in Inland Valleys: A Study From Côte d'Ivoire and Ghana - Alemayehu, Tesfahun; Assogba, Guy Marius; Gabbert, Silke; Giller, Ken E.; Hammond, James; Arouna, Aminou; Dossou-Yovo, Elliott Ronald; Ven, Gerrie W. J. van de (Frontiers in Sustainable Food Systems, 2022)
Inland valleys in West African countries have increasingly been used for crop production, including rice cultivation. Though it is widely assumed that inland valleys have a high potential to contribute to food security of West African countries, a comprehensive assessment of farming systems addressing agricultural, institutional, food security, poverty, and ecosystem indicators is still lacking. This study characterizes inland valleys' smallholder farm households at the regional and farm type level in Côte d'Ivoire and Ghana. Specifically, a farm typology is developed, and farm households are characterized with regard to demographic, agricultural, economic, and institutional indicators. Furthermore, farm households' food security and poverty status, and the importance of rice in the portfolio of crops, is assessed. Finally, farmers' awareness of different ecosystem services for their food security is examined. Four farm types are identified, i.e., farmers who rent all the land cultivated, farmers who own some land and rent extra land, farmers who own and cultivate all their land, and farmers cultivating only a part of the land they own. We find that the variation in farm households' demographic, economic, and institutional characteristics is greater between regions than within regions. Crop production for direct consumption or marketing, especially rice production, is the main contributor to daily energy requirements, followed by wild food consumed. Still, a substantial percentage of the farm households cannot meet minimum daily energy requirements. Farmers of all farm types, and in all regions, attach high relevance to inland valleys' provisioning ecosystem services, particularly the ability to provide food. In contrast, cultural ecosystem services seem less important. The results of the paper facilitate exploring effective strategies for improving food security of farm households, and for effectively managing natural resources on inland valleys in West African countries. Furthermore, interventions to improve national rice production need to acknowledge and preserve the diversity ecosystem services that inland valleys provide to smallholder farm households.